Expressed breast milk ( EBM );finder mobile application - Ramli, Nur Ariffah; Zulkefley, Siti Nur Amirah Aminah; Zulkifli, Zahidah (Faculty of Computing, Universiti Malaysia Pahang, 2019)
Expressed Breast Milk is breast milk pumped in a bag that can be stored and keep for future used. EBM Finder is an application that we develop to help mothers donate and find EBM at a specific platform as well as to provide a specific repository to keep records of the receiver and donator of the milk. The development of application is guided through System Development Life Cycle (SDLC) method which we identify the problems, gather the information, analyse and design the system, develop the software, test and maintain the system. This application expected to create an awareness on the importance of breast milk towards child development and to ease the process of finding and donating breast milk among Malaysian community.